Impact of Defaulting to Single-Lumen Peripherally Inserted Central Catheters on Patient Outcomes: An Interrupted Time Series Study. (9th April 2018) - Lam, Philip W; Volling, Cheryl; Chan, Tiffany; Wiggers, J Bradley; Castellani, Lucas; Wright, Julie; Peckham, Kenneth; Shadowitz, Steven; Tasker, Stephen; MacFadden, Derek R; Daneman, Nick; Gold, Wayne L; et al.
Abstract: Defaulting to single-lumen peripherally inserted central catheters (PICCs) ordered from non–critical care units resulted in a sustained reduction in PICC-related complications. This system of care is transferrable to other institutions, with potential for improved patient safety and efficiency in outpatient parenteral antimicrobial therapy clinics.